Injected Breast Materials: Review of Imaging Features and Characteristics. Issue 6 (16th June 2021) - Gao, Yukun; Karimova, E Jane; Phillips, Jordana; Fein-Zachary, Valerie; Dialani, Vandana; Mehta, Tejas S; Mehta, Rashmi; Slanetz, Priscilla J
Abstract: In the United States, silicone and saline breast implants with their familiar radiologic appearance are the mainstays of breast augmentation. However, less well-known sequelae of unconventional injected materials introduced for cosmetic and noncosmetic purposes may also be encountered on breast imaging—for example, free silicone, paraffin and/or oil, polyacrylamide gel, autologous fat, and hyaluronic acid, which are encountered in the setting of breast augmentation. Breast injection of go-yak is not cosmetic but also results in characteristic imaging findings. Breast changes due to extravasation of chemotherapy or interstitial brachytherapy can mimic the appearance of injected noncosmetic materials. Because many of these materials can mimic or obscure imaging findings of breast cancer, it is important to recognize their varied appearances and the limitations of imaging alone in delineating breast injection material from cancer. Given the relatively uncommon incidence of injected materials into the breast, this article aims to review the imaging appearance in order to aid radiologists in maximizing cancer detection and ensuring optimal patient management.